50 Poractant alfa versus bovine lipid extract surfactant for respiratory distress syndrome in preterm infants: A prospective comparative effectiveness cohort study. (29th October 2021) - Lemyre, Brigitte; Lacaze-Masmonteil, Thierry; Shah, Prakesh; Bodani, Jaya; Doucette, Stefanie; Dunn, Michael; Louis, Deepak; Monterrosa, Luis; Mukerji, Amit; Schmolzer, Georg; Singh, Balpreet; Wong, Jonathan; et al.
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: There is a paucity of comparative effectiveness data for bovine lipid extract surfactant (BLES) and poractant alfa (Curosurf). Objectives: To compare duration of respiratory support and short-term outcomes in very preterm infants treated with bovine lipid extract surfactant and poractant alfa. Design/Methods: We performed a prospective, multicentre, comparative effectiveness study. Thirteen Canadian level III neonatal intensive care units (NICUs) provided bovine lipid extract surfactant to infants born <32 weeks' gestational age (GA) for a set period of time in the year 2019 (3 to 9 months), then changed to poractant alfa for the remainder of the year. The primary outcome was total duration of respiratory support (invasive and non-invasive). We utilized the Canadian Neonatal Network database for all study data. Results: A total of 968 eligible infants (530 infants < 28 weeks' GA and 438 infants 28 0 -31 6 weeks' GA) were included, of which 494 received bovine lipid extract surfactant and 474 received poractant alfa. In unadjusted analysis, no difference was observed in total duration of any respiratory support (median 38 vs. 40.5 days). After adjusting for baseline characteristics and accounting for cluster effects, infants treated with poractant alfa spent a median of 4.16 fewer days on respiratory support (95% CI 0.05, 8.28 days). This reduction was observed in the subgroup of infants 28 0 -31 6 weeks' GA, but not in those < 28 weeks' GA, and was explained by their shorter time on non-invasive respiratory support. No differences were observed in the need to re-dose surfactant, hospital mortality, bronchopulmonary dysplasia, or length of stay in NICU. Conclusion: Administration of poractant alfa was associated with shorter median duration of respiratory support compared to bovine lipid extract surfactant in preterm neonates < 32 weeks' GA.